(2m+3)(6m-2)=

Simple and best practice solution for (2m+3)(6m-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2m+3)(6m-2)= equation:


Simplifying
(2m + 3)(6m + -2) = 0

Reorder the terms:
(3 + 2m)(6m + -2) = 0

Reorder the terms:
(3 + 2m)(-2 + 6m) = 0

Multiply (3 + 2m) * (-2 + 6m)
(3(-2 + 6m) + 2m * (-2 + 6m)) = 0
((-2 * 3 + 6m * 3) + 2m * (-2 + 6m)) = 0
((-6 + 18m) + 2m * (-2 + 6m)) = 0
(-6 + 18m + (-2 * 2m + 6m * 2m)) = 0
(-6 + 18m + (-4m + 12m2)) = 0

Combine like terms: 18m + -4m = 14m
(-6 + 14m + 12m2) = 0

Solving
-6 + 14m + 12m2 = 0

Solving for variable 'm'.

Factor out the Greatest Common Factor (GCF), '2'.
2(-3 + 7m + 6m2) = 0

Factor a trinomial.
2((-3 + -2m)(1 + -3m)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-3 + -2m)' equal to zero and attempt to solve: Simplifying -3 + -2m = 0 Solving -3 + -2m = 0 Move all terms containing m to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2m = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2m = 0 + 3 -2m = 0 + 3 Combine like terms: 0 + 3 = 3 -2m = 3 Divide each side by '-2'. m = -1.5 Simplifying m = -1.5

Subproblem 2

Set the factor '(1 + -3m)' equal to zero and attempt to solve: Simplifying 1 + -3m = 0 Solving 1 + -3m = 0 Move all terms containing m to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3m = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3m = 0 + -1 -3m = 0 + -1 Combine like terms: 0 + -1 = -1 -3m = -1 Divide each side by '-3'. m = 0.3333333333 Simplifying m = 0.3333333333

Solution

m = {-1.5, 0.3333333333}

See similar equations:

| 10x+-9x= | | 3r^2-9r-17=2r^2-5-8r | | 44x+7=73 | | 123+45=180 | | -2(8+4h)= | | x=5.6+1.4y | | 123+70=180 | | 2g+5=-3 | | (-7n/12)(9n/14) | | 9-5x=6x | | (2y-3)/(y+3)=5/7 | | 2h+5=3 | | 5x+3=10x+-7 | | 123+75=180 | | (-55)-(-88)= | | 6(7+x)+5x=0 | | -(8-4h)= | | 6f-1=2 | | 4s^4-17s^2+4=0 | | 176+4= | | 5x=7y+28 | | 9+5a=2a+5 | | 2x-1/3x=15 | | (3/8)(8/3)(n) | | (5/16)+(2/3)x=(1/4)-(1/6)x | | (-72)+36= | | (3/8)(8/3) | | A/4+7=22 | | 1-1/2-1/3 | | 2(0.6x+x)= | | (3k-3)(7k+7)= | | -8=p-5 |

Equations solver categories